1997
DOI: 10.1126/science.276.5319.1687
|View full text |Cite
|
Sign up to set email alerts
|

Multiple and Ancient Origins of the Domestic Dog

Abstract: Mitochondrial DNA control region sequences were analyzed from 162 wolves at 27 localities worldwide and from 140 domestic dogs representing 67 breeds. Sequences from both dogs and wolves showed considerable diversity and supported the hypothesis that wolves were the ancestors of dogs. Most dog sequences belonged to a divergent monophyletic clade sharing no sequences with wolves. The sequence divergence within this clade suggested that dogs originated more than 100,000 years before the present. Associations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
525
1
21

Year Published

1999
1999
2011
2011

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 880 publications
(587 citation statements)
references
References 15 publications
20
525
1
21
Order By: Relevance
“…The phylogenetic trees (Figure 2b) and haplotype network (Figure 3b) of the Tibetan Mastiff and domestic dogs constructed on the basis of COI barcoding were consistent with the COI gene. According to the NJ tree and network constructed by the COI gene sequence, we found 23 haplotypes clustered into four clades; the numbers of haplotypes (17, 73.91%) and individuals (66, 64.71%) of Clade A were more than those of Clades B and C, which is consistent with previous reports (Vilà et al, 1997;Savolainen et al, 2002). These results support the view of the East Asian origin of domestic dogs and the Clade A origin of the Tibetan Mastiff, which are consistent with the results according to the complete sequence of the mitochondrial genome (Li et al, 2011).…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…The phylogenetic trees (Figure 2b) and haplotype network (Figure 3b) of the Tibetan Mastiff and domestic dogs constructed on the basis of COI barcoding were consistent with the COI gene. According to the NJ tree and network constructed by the COI gene sequence, we found 23 haplotypes clustered into four clades; the numbers of haplotypes (17, 73.91%) and individuals (66, 64.71%) of Clade A were more than those of Clades B and C, which is consistent with previous reports (Vilà et al, 1997;Savolainen et al, 2002). These results support the view of the East Asian origin of domestic dogs and the Clade A origin of the Tibetan Mastiff, which are consistent with the results according to the complete sequence of the mitochondrial genome (Li et al, 2011).…”
Section: Resultssupporting
confidence: 90%
“…A total of 23 haplotypes were defined in the COI gene sequence of the Tibetan Mastiff and 76 domestic dog breeds (Table 1), and the haplotype percentage was 21.50%. The polymorphism was lower than that based on the mitochondrial displacement loop (D-loop; especially hypervariable region 1; Vilà et al, 1997;Savolainen et al, 2002;Luo, 2003), but higher than that based on the mitochondrial Cytb gene (Li et al, 2008). Vilà et al (1997) found 27 variable sites and identified 26 haplotypes in the 261-bp D-loop region with a 10.34% polymorphism loci percentage and an 18.57% haplotype percentage.…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…Thus, selection of a particular breed for a mapping study over other available breeds could dramatically reduce the work load and expense associated with the study, and judicious selection of breeds for studies of shared disorders becomes very important. Finally, this study demonstrated that haplotypes or blocks of alleles are frequently shared between dog breeds, a result that was not surprising given the recent evolution of the dog from the wolf 73,74 . This means that a single map and a single SNP chip will be useful for mapping studies in any breed of dog.…”
Section: Linkage Disequilibrium Facilitates Disease Gene Mappingsupporting
confidence: 56%